Awareness About Dental Caries Among Undergraduate Dental Students - A Survey - Samudhrasri S, Dr. Abirami Arthanari, (Drugs and Cell Therapies in Hematology, 2021)
Introduction: Dental caries is a biofilm mediated,sugar driven, multifactorial dynamic disease that results in the phasic demineralisation and remineralisation of dental hard tissues. It is a transmissible bacterial disease process caused by acids from bacterial metabolism, diffusing into enamel and dentine and dissolving the mineral. The aim of the present study is to evaluate awareness about dental caries among undergraduate dental students. Materials And Methods: A descriptive cross sectional study was conducted among the students. A self administered 15 item questionnaire was given to 100 students to assess their knowledge about dental caries and its diagnostic methods. One way analysis of variance and chi square test was done for statistical analysis. Confidence level and level of significance were set at 95% and 5% respectively. Results: Students answered the questions related to classes of cavities, methods to diagnose caries and its prevention. Most of the male students were aware of dental caries when compared to females and the value is statistically significant(p=0.201). Still more emphasis should be given to increase students' awareness of dietary guidelines for caries prevention.Since adequate knowledge of these modalities is paramount for graduating dentists. Conclusion: It can be concluded that most of the male students were aware of dental caries when compared to female students.